2014
DOI: 10.1002/chem.201402547
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Heat‐Set and Specific‐Ion‐Responsive Supramolecular Hydrogels Based on the Hofmeister Effect

Abstract: Smart supramolecular hydrogels have been prepared from a bolaamphiphilic L‐valine derivative in aqueous solutions of different salts. The hydrogels respond selectively to different ions and are either reinforced or weakened. In one case, in contrast to conventional systems, the hydrogels are formed upon heating of the system. The use of the hydrogels in the controlled release of an entrapped dye is described as a proof of the potential applications of these systems. The responsive hydrogels were rationally des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 61 publications
1
36
0
1
Order By: Relevance
“…Furthermore, the efficiency of the anions in promoting self‐assembly was in good agreement with the Hofmeister series . In another example, molecular hydrogels were prepared from a bolaamphiphilic l ‐valine derivative ( 5 ) in aqueous solutions of different salts . The hydrogels were found to respond selectively to different ions and were either reinforced or weakened by the presence of salts.…”
Section: Peptide‐based Molecular Gelssupporting
confidence: 59%
“…Furthermore, the efficiency of the anions in promoting self‐assembly was in good agreement with the Hofmeister series . In another example, molecular hydrogels were prepared from a bolaamphiphilic l ‐valine derivative ( 5 ) in aqueous solutions of different salts . The hydrogels were found to respond selectively to different ions and were either reinforced or weakened by the presence of salts.…”
Section: Peptide‐based Molecular Gelssupporting
confidence: 59%
“…[ c] Enantiomer ratios were determined by chiral HPLC. [19] as the phosphate ion belongs to the group of ions that usually lower the solubility of hydrophobic solutes in water,t ermed kosmotropic ions. [20] For the studied case, this effect is strongly active for both compounds 2 and 4.I ndeed, the 1 HNMR spectra of the two compounds in buffer at pH 7d id not showa ny signal correspondingt of ree compounds, revealing that the soluble fraction of both falls below the detection limit of this technique (< 5%), and therefore > 95 %o ft he catalyst molecules are in the non-protonated active form at that pH (the Supporting Information, Figures S17 and S18).…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…The large morphological and volume change at the LCST of PNIPAM‐based gels make mechanical studies meaningless. A series of studies on the Hofmeister effect on supramolecular hydrogels showed a dependence of the mechanical properties, but this was merely induced by the hugely different morphologies found for the different assembly conditions of the gels …”
Section: Introductionmentioning
confidence: 99%